Authoritarian reactions to terrorist threat: Who is being threatened, the Me or the We?. (7th February 2013) - Asbrock, Frank; Fritsche, Immo
<x xml:space="preserve">Abstract</x> Endorsement of authoritarian attitudes has been observed to increase under conditions of terrorist threat. However, it is not clear whether this effect is a genuine response to perceptions of personal or collective threat. We investigated this question in two experiments using German samples. In the first experiment (N = 144), both general and specific authoritarian tendencies increased after asking people to imagine that they were personally affected by terrorism. No such effect occurred when they were made to think about Germany as a whole being affected by terrorism. This finding was replicated and extended in a second experiment (N = 99), in which personal and collective threat were manipulated orthogonally. Authoritarian and ethnocentric (ingroup bias) reactions occurred only for people highly identified with their national ingroup under personal threat, indicating that authoritarian responses may operate as a group‐level coping strategy for a threat to the personal self. Again, we found no effects for collective threat. In both studies, authoritarianism mediated the effects of personal threat on more specific authoritarian and ethnocentric reactions. These results suggest that the effects of terrorist threat on authoritarianism can, at least in part, be attributed to a sense of personal insecurity, raised under conditions of terrorist threat. We discuss the present findings with regard to basic sociomotivational processes (e.g., group‐based control restoration, terror management) and how these may relate to recent models of authoritarianism.